Use of Multimedia Tools to Assist English Language Teaching and Learning as a Second Language - Jalaluddin, Mohammad (Technium Social Sciences Journal, 2023)
Course books are the most popular way to learn foreign languages. However, in the 21st century, there are other ways to learn languages, such as multimedia tools. The use of the Internet, newspapers, radio, or television can be an alternative to traditional language learning methods.The rapid advancement of science and technology, such as multimedia technology, has made it possible to explore this new teaching method more effectively. In reality, multimedia technology plays a vital role in the teaching of English language, particularly in the context of non-native speaking English. It also helps non-native English speakers of language teachers to understand how to use it effectively. The use of multimedia in foreign language teaching has grown steadily, and it has greatly improved the quality of teaching and learning. To effectively teach a foreign language, the traditional method is insufficient. We ought to reconsider the way we teach and accept their impersonal quality as a type of instruction. Thus, we can legitimately use contemporary educational technology to achieve the goal of teaching languages. Nowadays, almost everyone uses multimedia tools to help them with daily tasks. For example, some people get ready to leave the house to the beat of the radio’s music, while others can’t imagine having breakfast without reading the newspaper and so on.